Dynamics of comprehensive physical fitness in artistic gymnasts aged 7-10 years - Boraczyńska, Sandra; Boraczyński, Tomasz; Boraczyński, Michał; Michels, Anna (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: The aim of the study was to evaluate the somatic development and comprehensive physical fitness of artistic gymnasts aged 7-10 years. Materials and methods: Gymnasts (n = 307), split up into four age groups performed eight Eurofit tests. The results were evaluated in points according to the development standards prepared in scale T for the Polish girls population. Results : The gymnasts obtained the highest growth rate in balance test - FLB (13 points), arm and shoulder muscular endurance test - BAH (7 points) and speed of the upper limb movement test - PLT (4 points) out of eight physical fitness tests. Conclusions. High and very high level of performance in the six Eurofit tests and increased total number of points in the subsequent age groups of artistic gymnasts proved high effectiveness of training in shaping the key components of a comprehensive physical fitness in artistic gymnastics - balance, strength, endurance, speed and flexibility. Relatively little progress in isometric hand strength (HGR) and standing broad jump (SBJ) suggests a significant influence of genetic factors on the level of these abilities. The results provide an objective information useful in optimizing control system of training effects in comprehensive physical fitness and optimization of artistic gymnasts training at the comprehensive stage of sports training.